Personal finance - Kapoor, Jack R. (McGraw-Hill Irwin, 2009)
Personal Finance, Ninth Edition provides many financial planning tools using a step-by-step approach to help students identify and evaluate choices as well as understand the consequences of decisions in terms of opportunity costs.